Blockholding, ownership horizon, and firms' ESG performance - Chowdhury, Abu; Vaihekoski, Mika; Yahya, Habeeb (Taylor & Francis, 2026)
This paper examines whether blockholders and their investment horizon influence firms' ESG performance in the Nordic countries. We use ownership data for the three largest owners of the publicly listed firms, and we find a positive, statistically significant association between the ownership of the top two blockholders and a firm's ESG scores. Closer analysis reveals that the impact is driven by long-term blockholders. The effect concentrates on the environmental and social pillars, rather than governance. Our study contributes to the literature by showing that long-term horizons of the largest blockholders, identified through observed holding periods, play a key role in shaping firms' ESG performance in the Nordic context. The results imply that boards, policymakers, and stewardship teams can leverage stable, long-horizon blockholders to advance environmental and social efforts, even when governance scores do not move in tandem.